THE IMPACT OF FINANCIAL RATIO INDICATORS ON PROFITABILITY IN SHARIA BANKS IN INDONESIA PERIOD 2019-2023 - Mulyawisdawati, Richa Angkita; Khoiriyah, Lu'luatul; Inayati, Anindya Aryu; Imtihanah, Ani Nurul (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2025)
This study aims to analyze the impact of financial ratios on the profitability of Sharia banks in Indonesia during the period 2019–2023. The financial ratios used in this research include Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (BOPO), and Net Operating Margin (NOM). Profitability is measured by Return on Assets (ROA). The research method employed is a quantitative approach with panel data analysis using secondary data obtained from the annual financial reports of Sharia Commercial Banks published by the Financial Services Authority (OJK). The results of the partial research (t-test) indicate that the CAR, FDR and NOM variables have positive and significant effect on profitability (ROA). Meanwhile, the NPF and BOPO variables do not have a significant effect on ROA.